Moisture Loss Models of Sweet Potato, Cassava and Taro During Frying - Ratnaningsih Ratnaningsih; Djajeng Sumangat; Budi Rahardjo (agriTECH, 2011)
Sweet potato, cassava and taro were cut into stick (0.01 x 0.01 x 0.05 m) and deep fat fried at three temperatures (160,170 and 180 ºC) for 0 to 360 s. The effects of these cooking methods on moisture loss characteristics were evaluated. The rapid moisture loss from the sticks within the first 100 s of deep fat frying followed by considerably reduced rates. Moisture diffusivity in sweet potato, cassava and taro sticks were evaluated using analytical solution of Fick’s second law diffusion equation. Moisture diffusivities  were ranging from 1.43x10-8  to 1.99x10-8  m2/s, 1.38x10-8  to 2.25x10-8 m2/s, and 3.08x10-8 to 5.25x10-8 m2/s respectively, at temperatures ranging from 160 to 180 ºC, for sweetpotato, cassava and taro. Corresponding activation energies for moisture transfer were 26.88; 39.61 and 43.51 kJ/mol for sweet potato, cassava and taro deep fat frying, respectively.